Dragon Meets Camel: An Exploration of China’s Engagement with Eritrea - Fikresus Amahazion (Journal of Social and Development Sciences, 2022)
Over the past several decades, the People’s Republic of China’s engagement with African countries has grown tremendously. China has emerged as Africa’s largest trading partner, while Chinese investment in and lending to African countries has grown rapidly. In Eritrea, a young, developing country located in the Horn of Africa, Chinese involvement has also considerably increased in recent years. However, although there has been extensive study of China’s partnerships across the continent, very little work has been dedicated to examining its ties with Eritrea. What are the history and current scale of involvement? What has been the impact of this engagement on Eritrean society? What are locals’ overall perceptions about the relationship or about China more generally? Utilizing a mix of qualitative research methods, including surveys, the current paper explores China’s engagement with Eritrea, adding to the voluminous, ever-growing body of literature and helping to diversify and deepen understanding of this important topic. Additionally, although various narratives about the China-Africa relationship have arisen, often led and framed by non-Africans, the present study broadens the discussion by offering local, African perspectives on China-Africa links. Engagement and cooperation between China and Eritrea are longstanding and extend to numerous areas, driven by a range of interests, while local perceptions are quite nuanced and largely consistent with many cross-national studies.